Fabrication of a flexible polyimide-based electrostatically actuated MEMS relay. (29th June 2018) - Liu, Junshan; Shu, Zhen; Wang, Chao; Shan, Han; Yin, Penghe; Zhang, Fengtian; Zhang, Yue; Xiong, Zhuang; Du, Liqun; Tang, Bin; Xu, Zheng
Abstract: A four-photomask method for fabricating a polyimide (PI)-based electrostatically actuated MEMS relay is presented. The processes for patterning the SiO2 sacrificial layer and curing the PI layer for making the movable structure were optimized. The substrate and the movable structure of the relay were all made of PI, and thus the relay exhibited excellent flexibility and could be used for flexible electronics. Moreover, using PI as the substrate of the drain electrode significantly reduced the effective hardness of the contact material. The hardness of a Au film on a PI substrate was only 42% of that of the Au film on a silicon substrate. In turn, the decrease of the hardness of the contact material contributed to obtaining a lower contact resistance. The contact resistance of the MEMS relay with a PI substrate was less than half of that of the MEMS relay with a silicon substrate.